Identification of Eight Spliceogenic Variants in BRCA2 Exon 16 by Minigene Assays - Fraile-Bethencourt, Eugenia; Valenzuela-Palomo, Alberto; Díez-Gómez, Beatriz; Acedo, Alberto; Velasco, Eladio A. (Frontiers in Genetics, 2018)
Genetic testing of BRCA1 and BRCA2 identifies a large number of variants of uncertain clinical significance (VUS) whose functional and clinical interpretations pose a challenge for genetic counselling. Interestingly, a relevant fraction of DNA variants can disrupt the splicing process in cancer susceptibility genes. We have tested more than 200 variants throughout 19 BRCA2 exons mostly by minigene assays, 54% of which displayed aberrant splicing, thus confirming the utility of this assay to check genetic variants in the absence of patient RNA. Our goal was to investigate BRCA2 exon 16 with a view to characterizing spliceogenic variants recorded at the mutational databases. Seventy-two different BIC and UMD variants were analyzed with NNSplice and Human Splicing Finder, 12 of which were selected because they were predicted to disrupt essential splice motifs: canonical splice sites (ss; 8 variants) and ESE/ESS (4 variants). These 12 candidate variants were introduced into the BRCA2 minigene with 7 exons (14 to 20) by site-directed mutagenesis and then transfected into MCF-7 cells. Seven variants (6 intronic and 1 missense) induced complete abnormal splicing patterns: c.7618-2A>T, c.7618-2A>G, c.7618-1G>C, c.7618-1G>A, c.7805G>C, c.7805+1G>A and c.7805+3A>C, as well as a partial anomalous outcome by c.7802A>G. They generated at least 10 different transcripts: ∆16p44 (alternative 3’ss 44-nt downstream; acceptor variants), ∆16 (exon 16-skipping; donor variants), ∆16p55 (alternative 3’ss 55-nt downstream), ∆16q4 (alternative 5’ss 4-nt upstream), ∆16q100 (alternative 5’ss 4-nt upstream), ▼16q20 (alternative 5’ss 20-nt downstream) as well as minor (∆16p93 and ∆16,17p69) and uncharacterized transcripts of 893 and 954 nucleotides. Isoforms ∆16p44, ∆16, ∆16p55, ∆16q4, ∆16q100 and▼16q20 introduced premature termination codons which presumably inactivate BRCA2. According to the guidelines the American College of Medical Genetics and Genomics (ACMG) these eight variants could be classified as pathogenic or likely pathogenic whereas the Evidence-based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) rules suggested seven class 4 and one class 3 variants. In conclusion, our study highlights the relevance of splicing functional assays by hybrid minigenes for the clinical classification of genetic variations. Hence, we provide new data about spliceogenic variants of BRCA2 exon 16 that are directly correlated with breast cancer susceptibility.